2020
DOI: 10.14569/ijacsa.2020.0110259
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Prediction Model’s Credit Risk: The Implementation of the Backward Elimination and Forward Regression Method

Abstract: The purpose of this paper is to verify whether there is a relationship between credit risk, main threat to the banks, and the demographic, marital, cultural and socioeconomic characteristics of a sample of 40 credit applicants, by using the optimal backward elimination model and the forward regression method. Following the statistical modeling, the final result allows us to know the variables that have a degree of significance lower than 5%, and therefore a significant relationship with the credit risk, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A quadratic regression model was initially suggested and adopted as its R-squared statistic is above 90%. In the analysis of variance (ANOVA), Backward Elimination method was used to improve and determine the final modified regression model [14].…”
Section: Resultsmentioning
confidence: 99%
“…A quadratic regression model was initially suggested and adopted as its R-squared statistic is above 90%. In the analysis of variance (ANOVA), Backward Elimination method was used to improve and determine the final modified regression model [14].…”
Section: Resultsmentioning
confidence: 99%
“…This process continues until a model is found that only contains variables that significantly affect the dependent variable. [21], [22] 2) Forward Selection Forward Selection is the opposite of the Backward Elimination method, where features or independent variables are selected in stages. The independent variables are entered into the model in stages, starting with the variable with the highest correlation to the positive and negative dependent variables.…”
Section: ) Backward Eliminationmentioning
confidence: 99%
“…CRA systems appeared at the beginning of the 2000s, with the development of new technologies and financial institutions' need for information systems that could conduct CRA. The first CRA systems implemented algorithms and statistical techniques based on financial models to determine potential debtors [17]. Later, ML-based models appeared and evolved into AI models that use big data techniques to process big databases, which is necessary to improve the results of the assessment [18].…”
Section: Introductionmentioning
confidence: 99%